Taʾthīr istikhdām al-qirāʾah al-muṣawwarah ʿalā al-qudrah maharat al-qirāʾah fī taʿlīm al-ʿArabiyyah li-ṭālibāt al-faṣl al-ʿāshir fī al-madrasah al-ʿāliyyah al-islāmiyyah al-ahliyyah "Muʿallimāt" Cukir, Jombang - Jihanul Khofifah; M. Arif Setyabudi (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
Arabic has four skills, namely reading skills, listening skills, speaking skills and writing skills. And Arabic illustrated reading affects reading skills in Arabic lessons for class x students. and because of this, the researcher wanted to know the effect of illustrated reading on maharahqira’ah or the ability to read Arabic texts in class X students at Madrasah Aliyah, Cukir College, Jombang. Here the researcher uses a quantitative approach with a correlational approach and data collection, in this study there are three namely notes, tests, and documents. The research results can be concluded as follows: 1) Students of class X religion at Madrasah Aliyah, CukirJombang, are able to read illustrated readings well, fluently and in accordance with intonation rules, they can understand text in Arabic by using pictures, 2) Students of class X religion at Madrasah Aliyah, CukirJombang, in learning Arabic are able to apply maharahqira'ah or reading skills in Arabic illustrated readings After the Spearman correlation test was carried out, the sig value was 0.002 which means (H0) was rejected and (HA) was accepted and the Spearman correlation coefficient value which means the effect of illustrated reading on the ability of maharahqira’ah students of class X Madrasah Aliyah, JombangMuallimat College is strong.